The effects of peer-versus self-editing on learner autonomy in ESL writing - Diab, Nuwar Mawlawi (2009)
This thesis reports on an action research study carried out with students attending an English medium university. The action research comprised three cycles, each presented here as a Study. Study One, which investigated the effects of peer-editing on students’ revised drafts as well as on new essays, revealed that the students did not benefit from peer feedback in improving their revised drafts. However, peer-editing helped them write new better quality essays. Results of Study One led to Study Two, which investigated the reasons for the students’ failure to benefit from their peers’ feedback in revising their essays. It showed that the students’ culture of learning played a major role in their giving and receiving of peer feedback. The insight gained from Study Two led me to modify my method of teaching peer-editing before embarking on Study Three, which investigated the same questions as Study One but with two new aspects: 1) Study Three employed an experimental group which engaged in peer-editing, and a comparison group which practiced self-editing, and compared the effects of peer-editing to that of self-editing on the students’ writing. 2) It also tested the students’ ability to correct specific types of language error. Compared to the comparison group, the experimental group significantly improved their writing in revised drafts as well as in new essays. Since both groups received teacher instruction, but only the experimental group had engaged in peer-editing, these results may be attributed to peer-editing. More specifically, the experimental group significantly reduced rule-based language errors in revised drafts but not in new essays. However, non rule-based errors were not significantly reduced either in revised drafts or in new essays. The thesis grounds the results of this action research study in a socio-cognitive theoretical framework of Second Language Acquisition. The study contributes to research by demonstrating the important role of both teacher intervention and peer interaction in developing the students’ writing skills in a way which may lead them to become autonomous writers. It also has important pedagogical implications for teachers as it reveals the benefit of correcting specific, rather than all, language errors in order to bring about some language development in their students’ linguistic knowledge.